ERK1 and ERK2 Regulate Chondrocyte Terminal Differentiation During Endochondral Bone Formation. (May 2015) - Chen, Zhijun; Yue, Susan X; Zhou, Guang; Greenfield, Edward M; Murakami, Shunichi
ABSTRACT Chondrocytes in the epiphyseal cartilage undergo terminal differentiation prior to their removal through apoptosis. To examine the role of ERK1 and ERK2 in chondrocyte terminal differentiation, we generated Osterix (Osx)‐Cre; ERK1–/–; ERK2flox/flox mice (conditional knockout Osx [cKOosx]), in which ERK1 and ERK2 were deleted in hypertrophic chondrocytes. These cKOosx mice were grossly normal in size at birth, but by 3 weeks of age exhibited shorter long bones. Histological analysis in these mice revealed that the zone of hypertrophic chondrocytes in the growth plate was markedly expanded. In situ hybridization and quantitative real‐time PCR analyses demonstrated that Matrix metalloproteinase‐13 (Mmp13) and Osteopontin expression was significantly decreased, indicating impaired chondrocyte terminal differentiation. Moreover, Egr1 and Egr2, transcription factors whose expression is restricted to the last layers of hypertrophic chondrocytes in wild‐type mice, were also strongly downregulated in these cKOosx mice. In transient transfection experiments in the RCS rat chondrosarcoma cell line, the expression of Egr1, Egr2, or a constitutively active mutant of MEK1 increased the activity of an Osteopontin promoter, whereas the MEK1‐induced activation of the Osteopontin promoter was inhibited by the coexpression of Nab2, an Egr1 and Egr2 co‐repressor. These results suggest that MEK1‐ERK signaling activates the Osteopontin promoter in part through Egr1 and Egr2. Finally, our histological analysis of cKOosx mice demonstrated enchondroma‐like lesions in the bone marrow that are reminiscent of human metachondromatosis, a skeletal disorder caused by mutations in PTPN11. Our observations suggest that the development of enchondromas in metachondromatosis may be caused by reduced extracellular signal‐regulated kinase/mitogen‐activated protein kinase (ERK MAPK) signaling. © 2014 American Society for Bone and Mineral Research.